Sistem Monitoring Produksi Outsole Sepatu Di CV. Teja Rubber - Reno Setiawan; Puspita Nurul Sabrina; Fajri Rakhmat Umbara (Ikatan Ahli Informatika Indonesia, 2020)
In the development of advanced information technology, companies are often faced with rapid changes in the business environment, so companies need to carry out continuous monitoring and measurement of company performance. Monitoring is a cycle of activities that closely observe a situation or condition including certain activities. CV. Teja Rubber, is engaged in manufacturing rubber outsole by accepting customer orders that have been determined the size and color for shoes outsole to be made, has the activity of making shoes outsole from the beginning of raw materials to become an shoe outsole. However, in the production process there are still problems in monitoring the production process, namely the difficulty of getting information on the development of the production process causes difficulty in monitoring the development of the production process. Therefore, in supporting and improving the production process, namely by creating a monitoring system for shoes outsole production in CV. Teja Rubber. The system can manage the flow of information that can be known by all sections to monitor the course of production in accordance with the targeted and find out when the process is not appropriate so that it is easy to access information about the number of products produced, production time taken, and products that are not feasible so that production reports will be more effective and the production process can be controlled.